Clinical profile and outcome of snake bite in children - Dr. Balaji Bhusanpatnaik; Dr. Chandra Deve Varma BSK; Dr. N.V.Sujatha; Dr. T. Jogi Satyasree; Dr. Sreya. A; Dr. V. Priyanka (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Snake bite is generally considered to be a rural problem and has been linked with environmental and occupational condition is a neglected public health problem. This study was conducted to ascertain clinical profile, complication and outcome of snake bite in pediatric population. Methods: Retrospective observational study was done in Paediatrics wards and Paediatric Intensive care unit of tertiary care institute. A medical record files of 200 patients of snakebite, between the periods of January 2013 to August 2018 were recovered from Medical Record and Statistics Section of Institute. Files were analyzed for demographic data; variables included site of bite, time of bite, type of primary treatment and treatment provider, and type of snake poison, common symptoms suggestive of hematotoxicity, myotoxicity and neurotoxicity. Results: Out of total 200 patients, 59.0% were male and most of snake bites were seen in age group of 6-12 years. All bites were nonprovocative and in 57.5% lower limb was the commonest site of bite. A 81.5% patient were primarily treated by medical personnel, 56.5% patients were received treatment within 1 hour of bite and hospitalized within 6 hours of bite. Cellulitis was commonest complication (39.0%) followed by vasculotoxicity (30%) and neuroparalysis in (27.5%), followed by respiratory paralysis in (19.0%),coagulation (17.0%). Renal replacement therapy was required in 6.5%, blood/blood product transfusion in 11% patients and case fatality rate was 11.5%. Conclusions: The most vulnerable to snake bites are boys aged more than 5 years. There is an urgent need to spread awareness among the community for avoidance of traditional treatment and any delay in medical intervention in snakebite incidents.